2019
DOI: 10.1101/800797
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-timescale hybrid components of the functional brain connectome: A bimodal EEG-fMRI decomposition

Abstract: Concurrent electroencephalography (EEG) and functional magnetic resonance imaging (fMRI) bridge brain connectivity across timescales. During concurrent EEG-fMRI resting-state recordings, whole-brain functional connectivity (FC) strength is spatially correlated across modalities. However, cross-modal investigations have commonly remained correlational, and joint analysis of EEG-fMRI connectivity is largely unexplored.Here we investigated if there exist (spatially) independent FC networks linked between modaliti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 56 publications
(91 reference statements)
2
14
0
Order By: Relevance
“…This suggests that part of the EEG FC is distinct from fMRI FC. This observation has also been confirmed by a study analysing phase-coupling ICA networks ( Wirsich et al, 2020 ). It is plausible that phase coupling FC captures networks that are distinct from fMRI, while amplitude coupling FC capture similar networks ( Brookes et al, 2011a , 2011b ; Hiltunen et al, 2014 ; Hipp and Siegel, 2015 ; Liu et al, 2018 , 2017 ; Pasquale et al, 2010 ).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…This suggests that part of the EEG FC is distinct from fMRI FC. This observation has also been confirmed by a study analysing phase-coupling ICA networks ( Wirsich et al, 2020 ). It is plausible that phase coupling FC captures networks that are distinct from fMRI, while amplitude coupling FC capture similar networks ( Brookes et al, 2011a , 2011b ; Hiltunen et al, 2014 ; Hipp and Siegel, 2015 ; Liu et al, 2018 , 2017 ; Pasquale et al, 2010 ).…”
Section: Discussionsupporting
confidence: 67%
“…Given the different physiological origin of EEG and fMRI as well as differences in connectivity measures ( Haufe et al, 2018 ; Siems and Siegel, 2020 ; Wirsich et al, 2020 ), it is not surprising that we do not find any similarities between the connectivity matrices. However, it has been shown that the two measures capture complementary information of connectivity ( Wirsich et al, 2017 ).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Beyond the static relationship of EEG and fMRI to structure, we also observed crossmodal linked dynamics (1 minute sliding window) (Wirsich et al, 2020b). While most work focused on crossmodal agreement of FC, we have equally shown that the crossmodal connectivity can be split up into a common and complimentary connectivity profile across different timescales (Wirsich et al, 2020a). A crucial open question is whether crossmodal dissimilarities arise mainly from differences in data quality and acquisition setup, or represent differences arising from measuring complementary multimodal aspects of brain functional connectivity (Sadaghiani and Wirsich, 2020).…”
Section: Introductionmentioning
confidence: 99%